Sliding wear analysis of cobalt based alloys in nuclear reactor conditions - McCarron, Ruby; Stewart, David; Shipway, Philip; Dini, Daniele (Elsevier, 2017)
The study of the wear behaviour of cobalt based alloys in nuclear reactor environmental conditions is the focus of this work. The alloys are used in components within reactors due to their excellent wear and corrosion resistance and their high hardness in the high pressure and temperature water facing environment. In the nuclear reactor core, cobalt is irradiated producing a highly penetrative gamma emitting isotope, cobalt 60 from stable cobalt 59. Wear of the cobalt alloys, producing wear debris, exacerbates this problem as it may be transported and deposited at various locations throughout the primary loop increasing the potential of radiation exposure. Removing this problem will require the removal of cobalt from the system.